Description of a Harmless Method for Determining Trenbolone Acetate Together with 17\(β\)-Trenbolone in Beef - Furusawa, Naoto (Current Advances in Chemistry and Biochemistry Vol. 9, 2021)
The simultaneous measurement of trenbolone acetate and 17\(β\)-trenbolone in cattle muscle is described using an affordable, safe, and rapid sample preparation procedure followed by reversed-phase high-performance liquid chromatography (HPLC). HPLC analysis with a photo-diode array detector was carried out on a short C1 column with an isocratic mobile phase. The method was validated through analyses of spiked samples, resulting recoveries (\(\ge\) 87.9%; relative standard deviations \(\le\) 3.4%), analytical total time (< 20 min/sample, where, a batch of 12 samples was completed in 2 hours), and quantitation limits (\(\le\) 1.8 ng/g). The proposed technique for determination of TBa and \(β\)-TB in beef (cattle muscle) is a useful tool for the routine residue monitoring in beef and the withdrawal control of beef farm. No harmful organic solvents and reagents were used at all.